Unlocking Logic: Exploring Fluid Mechanics Course Profiles to Boost Pre-Service Science Teachers’ Reasoning Skills - Diniya Diniya; Muslim Muslim; Rika Rafikah Agustin; Rini Solihat; Shirin Selimova (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Fluid mechanics is a discipline of applied mechanics that deals with the behavior of liquids and gases at rest or in motion and gases at rest or in motion. The aim of the current research is to get an in-depth picture of the science pre-service teachers’ (PST) logical thinking skill and the lecture profile in fluid mechanics. The subjects were selected from both the students and lecturer in Fluid Mechanics Course (FMC) in one of the science education departments at a state university in the city of Pekanbaru. Conducted through qualitative-descriptive methods, the data were collected through test, observation, interview and documentation. Research instruments include the logical thinking skill test (LTST) adapted from Edunitas, observation sheets, interview questions list, and question checklist. The LTST as quantitative data processed using descriptive statistics with the help of SPSS 26.0 and the qualitative data processed using Miles and Huberman method. Based on the results, the mean score of LTST is 47,36. It can conclude that students' logical thinking is still low. Supported by observations and interviews, it disclosed that lectures still use the lecture method assisted by PhET simulation media while students only listen. Based on the question checklist, the mid-term exam already encompasses to critical thinking skill but the examples and practice questions are still at cognitive level C3 according to Bloom’s Taxonomy. Thus, the current fluid mechanics has not been able to train students' critical thinking skills. Innovation is crucial needed in fluid mechanics learning to improve students’ critical thinking skills.